Involution of a Large Parotid Hemangioma with Oral Propranolol: An Illustrative Report and Review of the Literature. (25th November 2012) - Mantadakis, Elpis; Tsouvala, Emmanouela; Deftereos, Savas; Danielides, Vassilios; Chatzimichael, Athanassios
Abstract : Propranolol has emerged as a new treatment option for infantile hemangiomas. We describe a 20-month-old boy with a large right parotid hemangioma diagnosed at the age of 37 days. Starting at the age of 2.5 months, he received oral propranolol for 6.5 months. Although the mass regressed, it recurred when propranolol was discontinued. He was successfully retreated at the age of 11 months with propranolol for another 5.5 months without further recurrences. Treatment was tolerated well. Our paper and a review of the literature demonstrate that propranolol appears to be safe and effective for symptomatic infantile parotid gland hemangiomas.